Do Religious Beliefs Barrier the Coping Mechanisms for Parents of Children with Autism Spectrum Disorder? - Hüseyin Çaksen (Pakistan Journal of Medical & Health Sciences, 2024)
I read with great interest the paper titled “pilgrimage for an autism diagnosis: a study of Venezuelan parents’ experiences” by Montiel-Nava et al1. The authors reported that Venezuelan parents mentioned a generalized lack of autism awareness, an unsupportive school system, and judgment from their extended family. Most of the parents understandably attached spiritual meaning to having an autistic child and used their spiritual and religious beliefs to deal with negative emotions. The parents also thought that praying to Allah would help their child could overcome their problem. The authors suggested that cultural values and spiritual and religious beliefs will serve as both coping mechanisms and barriers to accessing services for Venezuelan parents of children with autism spectrum disorder (ASD). However, there are several studies performed in different societies in the literature showing parents’ religious beliefs helped them to overcome difficulties at the time of diagnosis and during therapy of autism2.